Stabilisasi STABILISASI TANAH LATERIT DENGAN ABU SEKAM PADI DAN SERBUK BATU BATA UNTUK MENINGKATKAN DAYA DUKUNG TANAH: 1. Pendahuluan - Nizar; Ayub K. Moambura; Dinda Nurjanah; Fortunata Meikalista Marwan (Construction and Material Journal, 2026)
Lateritic soil is formed in tropical regions with high levels of weathering, is rich in iron, and is frequently used as landfill material. Lateritic soil in Peniraman, Sungai Pinyuh District, Mempawah is commonly utilized for landfill purpose; however, it has a low bearing capacity and is highly susceptible to moisture. In this study, an original soil sample was mixed with rice husk ash and brick powder at variations of 4%, 6%, 8%, 10%, and 12%. Rice husk ash was selected due to its high silica content, which has the potential to act as a pozzolanic material. Brick powder was chosen because it contains silica, alumina, and lime (CaO). The results showed that soil characteristics were effectively improved with the 4%-8% variations, with the 4% variation identified as the optimum level based on CBR test results. However, a decrease in soil performance was observed at the 10%-12% variations.